2021
DOI: 10.21203/rs.3.rs-1141407/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological Features of Neonates With COVID-19 Infection in Iran

Abstract: Objective: Although, the COVID-19 Pandemic has drawn the attention of physicians and researchers from all corners of the globe since it has been out broken in different countries, we have also started to invest more about the epidemiological features of neonates that had been affected by COVID-19 in Iran till now.Method: This is a cross-sectional retrospective study including all neonates from a National Registry supported by Iranian Maternal and Neonatal Network (IMaN). Since February 2020 till February 2021,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Also, UK databases have reported no deceased neonatal cases with a related cause to COVID-19 infection till April 2020 [15]. Meanwhile, the largest epidemiological study on 825 PCR-positive COVID-19 neonates in Iran reported a mortality rate of 10.3% with the need for respiratory support as the most important factor for neonatal death [18]. This is in line with our findings as all five deceased cases required respiratory support during hospitalization.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Also, UK databases have reported no deceased neonatal cases with a related cause to COVID-19 infection till April 2020 [15]. Meanwhile, the largest epidemiological study on 825 PCR-positive COVID-19 neonates in Iran reported a mortality rate of 10.3% with the need for respiratory support as the most important factor for neonatal death [18]. This is in line with our findings as all five deceased cases required respiratory support during hospitalization.…”
Section: Discussionsupporting
confidence: 89%
“…Neonatal laboratory tests in this study, including WBC count, lymphocyte percentages, platelet count, and Creactive protein, indicated that the majority of the cases were within the normal ranges, which confirms the findings of Al-Matary et al [14]. However, other studies are reporting elevated WBC count, C-reactive protein, lymphopenia, and thrombocytopenia [18,19,31,32].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations